MENINGKATKAN KETERAMPILAN BERPIDATO DENGAN MENERAPKAN METODE STRAIGHT - Trisno, Mohammad Hamid (sarasvati, 2020)
The purpose of this study was to describe the improvement of the speech skills of grade 9-A students of SMP Manbaul Ulum by applying the STRAIGHT method. This research uses classroom action research. The STRAIGHT method can improve students' speech skills, especially in SMP Manbaul Ulum with two cycles, cycle 1 and cycle 2. The target has been met with the majority of students above the KKM (70). Only 4 students or 17% have not completed out of 23 students. However, these 4 students have experienced improvements in each cycle. The results of learning the speech skills of Class 9-A students of SMP Manbaul after the application of the STRAIGHT method can be increased, both cycle 1 and cycle 2. So it can be said that the STRAIGHT method is successful in improving the speech skills of SMP Manbaul Ulum students.